The Acquisition of Orthographic Knowledge: Evidence from the Lexicality Effects on N400 - Tzeng, Yu-Lin; Hsu, Chun-Hsien; Huang, Yu-Chen; Lee, Chia-Ying (Frontiers in Psychology, 2017)
This study aimed to understand how reading ability shapes the lexicality effects on N400. Fifth-three typical developing children from 2nd to 6th grades were asked to perform the pronounceability judgment task on a set of Chinese real characters, pseudocharacters and noncharacters, as ERPs were recorded. The cluster-based permutation analysis revealed that children with low- to medium-reading ability showed greater negativity to noncharacters than to real characters and pseudocharacters in frontal sites from 300 to 450 ms, while children with high ability group showed a greater positivity to noncharacters than both real character and pseudocharacters at central to posterior sites. Furthermore, the linear mixed model (LMM) analysis was applied to investigate the relationship between lexicality effects on N400 and reading-related behavioral assessments on a set of standardized tests (including character recognition, vocabulary size, phonological awareness, and working memory). The results found that in children with lower reading ability, the N400 elicited by noncharacters becomes more negative in the frontal sites. For children with higher reading ability, the N400 elicited by noncharacters became more positive than that elicited by real characters or pseudocharacters in the posterior sites. These findings demonstrate the developmental changes in the lexicality effects on N400 as children become more advanced readers and suggest the lexicality effects on N400 can serve as neural markers for the evaluation of orthographic proficiency in reading development.